A Step Forward in Breast Cancer Research: From a Natural-Like Experimental Model to a Preliminary Photothermal Approach - Costa, Eduardo (2020)
Supplementary Materials - The following are available online at https://www.mdpi.com/1422-0067/21/24/9681/s1, Figure S1: GNPs’ size distribution by intensity (%) obtained by DLS.